EXPLORING THE CHANGING ROLE OF WOMEN IN DECISION-MAKING PROCESS AMONG PASHTUNS OF LOWER DIR - Bakht Roidar; Naila Hussain; Dr. Azizullah Jan (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examines the extent of Pakistani women’s participation in household decision-making relative to their husbands and other family members and determines its effects on the demand for children and contraceptive use in both urban and rural settings. The issue related women empowerment and decision-making power is universal. The issue is also burning in the targeted area of Lower Dir. The social role of women consists upon, Participation in Marriage ceremonies, Participation in Death Ceremonies, Participation in traditional and all types of ceremonies. Problems faced by women in their productive role-play; Women are less advantaged, lack of mobility, Limited education, no access to resources, invisible partners of development, low health, low levels of nutrition, high rates of mortality, male dominancy and patriarchy. To improve the role and status of Pakhtoon women it was recommended that women education should be improved, and they should be given equal participation in developmental activities of the society.